Can a quality improvement intervention improve person-centred maternity care in Kenya?. Issue 1 (31st December 2023) - Sudhinaraset, May; Giessler, Katie M.; Nakphong, Michelle Kao; Munson, Meghan M.; Golub, Ginger M.; Diamond-Smith, Nadia G.; Opot, James; Green, Cathy E.
Abstract: Few evidence-based interventions exist to improve person-centred maternity care in low-resource settings. This study aimed to understand whether a quality improvement (QI) intervention could improve person-centred maternity care (PCMC) experiences for women delivering in public health facilities in Kenya. A pre–post design was used to examine changes in PCMC scores across three intervention and matched control facilities at baseline ( n  = 491) and endline ( n  = 677). A QI intervention, using the Model for Improvement, was implemented in three public health facilities in Nairobi and Kiambu Counties in Kenya. Difference-in-difference analyses using models that included main effects of both treatment group and survey round was conducted to understand the impact of the intervention on PCMC scores. Findings suggest that intervention facilities' average total PCMC score decreased by 5.3 points post-intervention compared to baseline (95% CI: −8.8, −1.9) and relative to control facilities, holding socio-demographic and facility variables constant. Additionally, the intervention was significantly associated with a 1.8-point decrease in clinical quality index pre–post-intervention (95% CI: −2.9, −0.7), decreased odds of provider visits, and less likelihood to plan to use postpartum family planning. While improving the quality of women's experiences during childbirth is a critical component to ensure comprehensive, high-quality maternity care experiences and outcomes, further research is required to understand which intervention methods may be most appropriate to improve PCMC in resource-constrained settings.